Artificial Intelligence and Healthcare Delivery in Nigeria: Legal and Ethical Dimensions of Patients’ Rights to Safety - Ehirim, Ugochukwu Godspower (Elkuator Research and Publication, 2025)
The evolution of Artificial Intelligence (AI) has significantly transformed healthcare delivery in Nigeria by reshaping perceptions of medical negligence and enhancing diagnostic accuracy. Given Nigeria’s overstretched healthcare infrastructure and rapid population growth, AI presents critical opportunities to improve patient safety. However, its integration raises urgent legal and ethical challenges, including algorithmic bias, data privacy violations, and the erosion of fundamental medical principles such as informed consent and professional accountability. This article critically examines the intersection of AI innovation and Nigeria’s legal protection of patient safety and constitutional rights. Employing a qualitative methodology, it analyzes relevant statutes, constitutional provisions, and ethical frameworks related to privacy, non-discrimination, and medical regulation. The findings reveal a significant regulatory vacuum: AI is not addressed in sector-specific healthcare legislation, and existing constitutional safeguards are insufficient to mitigate the risks posed by autonomous and opaque AI systems. The article argues that this legal ambiguity increases patients’ exposure to unregulated AI practices and calls for a dedicated regulatory and legislative framework grounded in transparency, accountability, and human rights. Ultimately, the study concludes that AI should serve as a complementary—rather than a substitutive—tool in clinical decision-making and must be governed to uphold patient safety in Nigeria’s rapidly digitizing healthcare environment. [Perkembangan Kecerdasan Buatan (AI) telah mentransformasi sistem pelayanan kesehatan di Nigeria secara signifikan, dengan merekonstruksi pemahaman terhadap kelalaian medis serta meningkatkan ketepatan diagnosis. Dalam konteks infrastruktur kesehatan yang terbatas dan pertumbuhan populasi yang pesat, AI menawarkan peluang strategis untuk meningkatkan keselamatan pasien. Namun, integrasi AI ke dalam sistem kesehatan juga memunculkan tantangan hukum dan etika yang mendesak, termasuk bias algoritma, pelanggaran privasi data, serta erosi terhadap prinsip-prinsip mendasar dalam praktik medis seperti persetujuan berdasarkan informasi dan akuntabilitas profesional. Artikel ini mengkaji secara kritis persilangan antara inovasi AI dan perlindungan hukum atas keselamatan pasien serta hak-hak konstitusional di Nigeria. Dengan menggunakan metode kualitatif, kajian ini menganalisis peraturan perundang-undangan, ketentuan konstitusional, dan kerangka etik yang relevan terkait privasi, non-diskriminasi, dan regulasi layanan medis. Hasil temuan menunjukkan adanya kekosongan regulasi yang signifikan: AI belum diatur secara eksplisit dalam legislasi sektor kesehatan, dan perlindungan konstitusional yang ada belum memadai untuk menangani risiko yang ditimbulkan oleh sistem AI yang bersifat otonom dan tidak transparan. Artikel ini berargumen bahwa ambiguitas hukum tersebut meningkatkan kerentanan pasien terhadap praktik AI yang tidak diatur, dan oleh karena itu menyerukan pembentukan kerangka regulasi dan legislasi yang khusus, berbasis pada prinsip transparansi, akuntabilitas, dan penghormatan terhadap hak asasi manusia. Studi ini menyimpulkan bahwa AI harus diposisikan sebagai alat pelengkap—bukan pengganti—dalam pengambilan keputusan klinis, dan harus diatur secara ketat untuk menjamin keselamatan pasien dalam lingkungan layanan kesehatan digital yang berkembang pesat di Nigeria.]